2017
DOI: 10.1016/j.jcot.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Antiglide versus lateral plate fixation for Danis-Weber type B malleolar fractures caused by supination-external rotation injury

Abstract: In the present study, the outcome of the surgically treated Weber type B fractures caused by supination external rotation injury was comparable in both groups. The antiglide plate fixation showed no signs of peroneal tendinopathy, low rate of complications. We believe this technique is safe and a good method of fixation as well as traditional lateral plating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
0
9
2
1
Order By: Relevance
“…This conforms with other workers reported a female predominance such as Gauthe R. et al, [19] in a retrospective study included 477 patients 81% were female and Beris AE et al, [20] where 88% of fractures were in women with male to female ratio (1:1.57), this could be due to underlying osteopenia or osteoporosis in the female population with ages more than 45 years. This was in contrast to the study of Miroslav Kilian et al, [21] reported male predominance (54.2%), with male to female ratio (1.2:1), Rajiv et al, [13] (62.3%) were males, with male to female ratio (1.65:1) and Santosh S. et al, [15] male to female ratio (1.4:1).…”
Section: Discussioncontrasting
confidence: 74%
“…This conforms with other workers reported a female predominance such as Gauthe R. et al, [19] in a retrospective study included 477 patients 81% were female and Beris AE et al, [20] where 88% of fractures were in women with male to female ratio (1:1.57), this could be due to underlying osteopenia or osteoporosis in the female population with ages more than 45 years. This was in contrast to the study of Miroslav Kilian et al, [21] reported male predominance (54.2%), with male to female ratio (1.2:1), Rajiv et al, [13] (62.3%) were males, with male to female ratio (1.65:1) and Santosh S. et al, [15] male to female ratio (1.4:1).…”
Section: Discussioncontrasting
confidence: 74%
“…A prospective study by Kilian et al [ 18 ] found no significant difference in the AOFAS score of patients who underwent anti-glide (93.7±6.1; range 85-100) or lateral plate fixation of Weber B malleolus fractures (94.5±6.0; range 85-100) (p = 0.37). However, lag screws were applied in some patients who underwent anti-glide operation, which may have confounded the results.…”
Section: Discussionmentioning
confidence: 99%
“… 98 Posterolateral and posterior antiglide plate fixation led to satisfactory clinical and radiological outcome comparable to lateral plating. 99 101 A significant complication of posterolateral plating is a peroneal tendon lesion, that can lead to high rates of hardware removal. 102 But the more currently conducted studies report a low complication rate, including minimal presence of peroneal lesions.…”
Section: Operative Treatmentmentioning
confidence: 99%
“… 102 But the more currently conducted studies report a low complication rate, including minimal presence of peroneal lesions. 99 , 103 The antiglide plate can be inserted via a lateral or posterolateral approach, depending on the fracture configuration. A posterolateral approach is used in case of a concomitant fracture of the posterior malleolus requiring open reduction and internal fixation.…”
Section: Operative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation